Purple wheat alleviates dyslipidaemia in rat model - LAN,Suque (2022)
Abstract To study the exact effect of purple wheat (PW) on dyslipidaemia in rats so as to lay the foundation of a dietary therapy for hyperlipidaemia. A total of 42 rats were randomly divided into two groups: normal control group (NC) consisting of 12 rats were fed with standard diet in the whole testing process, the other group rats were fed with high-fat diet to induce dyslipidaemia. The dyslipidaemic rats were averagely divided into three groups: dyslipidaemia control group (DC) with 60% common wheat flour, PW1 group with diet containing 60% purple wheat Jizimai1 flour, PW3 group with 60% purple wheat Jizimai3 flour. Six weeks later, the weight-gain-ratio of the rats in PW1 and PW3 groups were lower as compared to the rats in DC and NC groups. Further, we found that the levels of triglyceride, total cholesterol and low-density lipoprotein in the PW1 and PW3 groups were significantly reduced to almost that of normal levels. Finally, the results of hematoxylin and eosin staining showed that intaking of Jizimai1 and Jizimai3 could repair hepatocyte steatosis and kidney injury due to dyslipidaemia. Purple wheat diet therapy reduced lipid metabolism disorders and the liver tissue and renal injury in hyperlipidaemic rats.